Challenges and Opportunities for the Implementation of Internal Audit to Realize Good University Governance in Private Universities in Central Java - Yodianti, Nofalina; Nugraheni, Bernadia Linggar Yekti (LP3M Universitas Putra Bangsa, 2023)
This study aims to investigate the efforts and commitments, challenges, and opportunities for the implementation of financial internal audits at Private Universities in Central Java. This study used a qualitative method by conducting interviews with members of the Internal Supervisory Unit at four private universities in Central Java that were accredited as superior. Private universities’ efforts and commitments were analyzed using institutional work theory, while challenges and opportunities were analyzed using institutional logic theory. The results showed that private universities' efforts to implement financial internal audits were realized with the motivation to implement Government regulations related to the accreditation of private universities. The commitment of private universities is indicated by the preparation of Standards of Operations (SOPs) for the implementation of internal audits and the inculcation of organizational culture. The challenges faced by private universities are limited human resources and information system technology. The opportunities that private universities have are an independent internal audit body and the Rector's open and transformative leadership style. The implementation of internal financial audits at private universities requires effort and commitment from the Rector and members of the organization to face challenges both from within and from outside.